Inactivation Effect of Standard and Fractionated Electron Beam Irradiation on Enveloped and Non-Enveloped Viruses in a Tendon Transplant Model - Schmidt, Tanja (S. Karger GmbH, 2012)
BACKGROUND: For increasing allograft tendon safety in reconstructive surgery, an effective sterilization method achieving sterility assurance including viruses without impairing the grafts properties is needed. Fractionated Electron Beam (Ebeam) has shown promising in vitro results. The proof of sufficient virus inactivation is a central part of the process validation. METHODS: The Ebeam irradiation of the investigated viruses was performed in an optimized manner (oxygen content < 0.1%, −78 °C). Using principles of a tendon model the virus inactivation kinetics for HIV-2, HAV, pseudorabies virus (PRV) and porcine parvovirus (PPV) were calculated as TCID(50)/ml and D(10) value (kGy) for the fractionated (10 × 3.4 kGy) and the standard (1 × 34 kGy) Ebeam irradiation. RESULTS: All viruses showed comparable D(10) values for both Ebeam treatments. For sufficient virus titer reduction of 4 log(10) TCID(50)/ml, a dose of 34 kGy of the fractionated Ebeam irradiation was necessary in case of HIV-2, which was the most resistant virus investigated in this study. CONCLUSION: The fractionated and the standard Ebeam irradiation procedure revealed comparable and sufficient virus inactivation capacities. In combination with the known good biomechanical properties of fractionated Ebeam irradiated tendons, this method could be a safe and effective option for the terminal sterilization of soft tissue allografts.